2010
DOI: 10.1167/iovs.09-4608
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Induced Relaxation of Porcine Retinal Arterioles In Vitro Depends on Prostaglandin E Synthesized in the Perivascular Retinal Tissue

Abstract: ATP-induced vasodilation depends on the production of PGE in the perivascular retina. However, the regulation of retinal arteriolar tone involves COX products other than PGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
(42 reference statements)
3
26
0
Order By: Relevance
“…The present study confirms results from previous studies that PGE 2 can induce concentration dependent relaxation and PGF 2 a a less pronounced contraction of porcine retinal arterioles in vitro (Holmgaard and Bek, 2010;Misfeldt et al, 2010a;Yu et al, 2001). The protocol used to study the effects of the two prostaglandins was designed to elicit opposite tone responses which required that the relaxing effect of PGE 2 was studied after pre-contraction (Holmgaard and Bek, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study confirms results from previous studies that PGE 2 can induce concentration dependent relaxation and PGF 2 a a less pronounced contraction of porcine retinal arterioles in vitro (Holmgaard and Bek, 2010;Misfeldt et al, 2010a;Yu et al, 2001). The protocol used to study the effects of the two prostaglandins was designed to elicit opposite tone responses which required that the relaxing effect of PGE 2 was studied after pre-contraction (Holmgaard and Bek, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…A possible involvement of PVCs in the regulation of retinal vascular tone might be confirmed if the activity of these cells differed after the addition of compounds stimulating respectively relaxation or contraction. Previous studies have shown that PGE 2 can induce relaxation of retinal arterioles and interferes with the effect of adenosine on vascular tone, whereas PGF 2 a can induce contraction of retinal arterioles (Holmgaard and Bek, 2010;Nielsen and Nyborg, 1990). Therefore, the effects of PGE 2 and PGF 2 a on vascular tone and calcium activity in PVC in porcine retinal arterioles were studied in vitro in a confocal myograph after the addition of the ryanodine receptor blocker ryanodine, the L-type Ca 2þ channel blocker nifedipine, the non-specific cation channel blocker LOE908, the sarcoplasmic reticulum Ca 2þ -ATPase (SERCA) blocker CPA, and the inositol triphosphate receptor (IP 3 R) and transient receptor potential (TRP) ion channel blocker 2-APB.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reduction of relaxation was observed in the presence of the EP 1 receptor antagonist SC 19220 which suggests that the effect had been mediated by prostaglandin E or other prostaglandins acting on this receptor in the vascular wall. Although a study has shown that prostaglandin E may elicit constriction of retinal arterioles [27], the present findings are consistent with several previous studies using the same model on both retinal and ciliary porcine arterioles [5,28,29]. Since ATP-γS-induced relaxation was unaffected by ibuprofen and EP 1 receptor antagonism, it is likely that the effect had been mediated by a degradation product from ATP.…”
Section: Discussionsupporting
confidence: 92%
“…The significance of these measures was confirmed by the increasing vasorelaxation induced by ATP during the implementation of the method until a reproducible effect was obtained. In a previous study where these precautions were not fully met, we found that the blocking effect of SC 19220 on ATP-induced vasorelaxation to some extent depended on the perivascular retinal tissue [5] which might have been due to an effect of ATP degradation products. Additionally, the EP 2 receptor antagonist PF-04418948 had no effect on ATP- and ATP-γS-induced relaxation which suggests that this receptor was not involved in ATP-induced relaxation of retinal arterioles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation